THE UTILIZATION OF THERMOPHILIC PROTEASE WHICH LIFE IN HOT SPRING CANGAR BATU MALANG - Rudiana Agustini (Universitas Gadjah Mada, 2006)
Thermophile protease has economic value, because this enzyme is useful on all kind of industry that used high temperature on it production process. The thermophile has been isolated from hot water spring at Cangar Batu Malang called CG-10 isolate. The characteristic of CG-10 are; bolt colony has a brown-white colour, rod form cels with size 6-14 µm and Gram positive. Identification with 16S-rRNA gene of their isolate shows 98.305% similarity with B. caldoxylolyticus. The protease characteristic of CG-10 isolate, fractionated by ammonium sulfate 35% (w/v), centrifuged by 4000 rpm of speed for 15 minute, (1) has optimum temperature of 80oC; (2) has optimum pH 8, (3) can survive until 60 minutes of incubation time at temperature 80oC , (4) the molecule weight of: 60-76 kDa with pH1 value between 7.5 - 8.20, (5) this protease is alkaline serine protease, and (6)Vmaks value 0.622 unit menit -1 and KM 9.8 µmol/L, so this CG-10 isolate protease can be use in detergent industry.